9x^2-4.5x-3.5=0

Simple and best practice solution for 9x^2-4.5x-3.5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x^2-4.5x-3.5=0 equation:


Simplifying
9x2 + -4.5x + -3.5 = 0

Reorder the terms:
-3.5 + -4.5x + 9x2 = 0

Solving
-3.5 + -4.5x + 9x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
9 the coefficient of the squared term: 

Divide each side by '9'.
-0.3888888889 + -0.5x + x2 = 0

Move the constant term to the right:

Add '0.3888888889' to each side of the equation.
-0.3888888889 + -0.5x + 0.3888888889 + x2 = 0 + 0.3888888889

Reorder the terms:
-0.3888888889 + 0.3888888889 + -0.5x + x2 = 0 + 0.3888888889

Combine like terms: -0.3888888889 + 0.3888888889 = 0.0000000000
0.0000000000 + -0.5x + x2 = 0 + 0.3888888889
-0.5x + x2 = 0 + 0.3888888889

Combine like terms: 0 + 0.3888888889 = 0.3888888889
-0.5x + x2 = 0.3888888889

The x term is -0.5x.  Take half its coefficient (-0.25).
Square it (0.0625) and add it to both sides.

Add '0.0625' to each side of the equation.
-0.5x + 0.0625 + x2 = 0.3888888889 + 0.0625

Reorder the terms:
0.0625 + -0.5x + x2 = 0.3888888889 + 0.0625

Combine like terms: 0.3888888889 + 0.0625 = 0.4513888889
0.0625 + -0.5x + x2 = 0.4513888889

Factor a perfect square on the left side:
(x + -0.25)(x + -0.25) = 0.4513888889

Calculate the square root of the right side: 0.671854812

Break this problem into two subproblems by setting 
(x + -0.25) equal to 0.671854812 and -0.671854812.

Subproblem 1

x + -0.25 = 0.671854812 Simplifying x + -0.25 = 0.671854812 Reorder the terms: -0.25 + x = 0.671854812 Solving -0.25 + x = 0.671854812 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.25' to each side of the equation. -0.25 + 0.25 + x = 0.671854812 + 0.25 Combine like terms: -0.25 + 0.25 = 0.00 0.00 + x = 0.671854812 + 0.25 x = 0.671854812 + 0.25 Combine like terms: 0.671854812 + 0.25 = 0.921854812 x = 0.921854812 Simplifying x = 0.921854812

Subproblem 2

x + -0.25 = -0.671854812 Simplifying x + -0.25 = -0.671854812 Reorder the terms: -0.25 + x = -0.671854812 Solving -0.25 + x = -0.671854812 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.25' to each side of the equation. -0.25 + 0.25 + x = -0.671854812 + 0.25 Combine like terms: -0.25 + 0.25 = 0.00 0.00 + x = -0.671854812 + 0.25 x = -0.671854812 + 0.25 Combine like terms: -0.671854812 + 0.25 = -0.421854812 x = -0.421854812 Simplifying x = -0.421854812

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.921854812, -0.421854812}

You can always share this solution

See similar equations:

| 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 | | x^2+6=6x^2-16 | | 16x^2-25=0 | | .66x^2-36=0 | | .66x^2-32=0 | | 2x^2+7x+3=0 | | 6x^2-47x=0 | | 3x^2-10x+3=0 |

Equations solver categories